2023
DOI: 10.1007/s00415-023-11764-5
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic grey matter alterations in ALS kindreds: a computational neuroimaging study of asymptomatic C9orf72 and SOD1 mutation carriers

Abstract: Background The characterisation of presymptomatic disease-burden patterns in asymptomatic mutation carriers has a dual academic and clinical relevance. The understanding of disease propagation mechanisms is of considerable conceptual interests, and defining the optimal time of pharmacological intervention is essential for improved clinical trial outcomes. Methods In a prospective, multimodal neuroimaging study, 22 asymptomatic C9orf72 GGGGCC hexanucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…With the advent of antisense oligonucleotide therapies, there is an ever-growing interest in presymptomatic processes in ALS. 30 Early subcortical changes have been consistently described in C9orf72 cohorts, often decades before predicted symptom onset, 31 and there is some data to suggest presymptomatic cerebellar disease burden also. Selective thalamic degeneration is also well described in ALS, 32 but it is typically linked to the concomitant degeneration of the frontal cortex, whereas here, we also capture thalamocerebellar structural disconnection at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of antisense oligonucleotide therapies, there is an ever-growing interest in presymptomatic processes in ALS. 30 Early subcortical changes have been consistently described in C9orf72 cohorts, often decades before predicted symptom onset, 31 and there is some data to suggest presymptomatic cerebellar disease burden also. Selective thalamic degeneration is also well described in ALS, 32 but it is typically linked to the concomitant degeneration of the frontal cortex, whereas here, we also capture thalamocerebellar structural disconnection at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, lower volumes of the thalamus have been reported in ALS patients with C9orf72 mutations, as well as in patients with ALS-FTD and FTD ( Agosta et al, 2017 , Bocchetta et al, 2018 , Nigri et al, 2023 , Schönecker et al, 2018 , van der Burgh et al, 2020 , Westeneng et al, 2016 ). Alterations in subcortical gray matter of the thalamus and the hippocampus were recently reported to occur in presymptomatic C9orf72 gene carriers and to precede changes in cortical gray matter ( Bede et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another study has suggested that the flail arm syndrome, a phenotypical variant of ALS, may show a similar degree of CST involvement as to that seem in patients with a ‘classical’ ALS presentation [ 133 ]. Subtle structural brain alterations have been shown to occur even in the earliest phases of the disease, as presymptomatic carriers of a C9orf72 expansion demonstrated significant, selective thalamic and focal hippocampal volume reductions [ 207 , 312 ].…”
Section: Advances In Neuroimagingmentioning
confidence: 99%